Physical-chemical characterization of processing tomato fruit - Braz, L. T. [UNESP]; Cintra, A. A D [UNESP]; Grilli, G. V G [UNESP]; Santos, G. M. [UNESP]; Braz, B. A. (My University, 2004)
Fruit of 28 tomato cultivars for industrial processing were characterized to identify cultivars with potential for in natura consumption. The experiment was carried out in Jaboticabal-SP, Brazil (21o15'22'' South, 48o18'58'' West, altitude 595 m), on a Haplorthox soil during June-December. The cultivars used in this study were: H 7155, Hypeel 108, Andino, U 573, H 9036, Ipa 6, H 9494, AG 33, Yuba, RPT 1294, AG 72, Peelmech, Curicó, Hypeel 45, RPT 1478, H 9492, H 9498, H 2710, Hitech 45, Halley, Botu 13, H 9553, U 646, NK 1570, AG 45, RPT 1095, RPT 1570 and PSX 37511. The experimental design was randomized blocks, replicated four times. Ten fruits per plot were analyzed, evaluating the following characteristics: shape (oblong or round); length and diameter (mm); external and internal coloration; presence of fissures; number of loci; pulp thickness (mm); soluble solids content (Brix) and total acidity. Only cultivars Hypeel 108, AG 72, NK 1570, RPT 1570 had oblong fruit. Cultivars which had pulp thicker than 5.5 mm, a characteristic which is directly related to fruit yield for industrial purposes were: Ipa 6, Andino, U 646, H 9553, RPT 1294 and Hypeel 108. Cultivars Ipa 6 and Andino also presented elevated values for length, diameter and pulp thickness, indicating them as quality material for industry or, alternatively, for in natura market. Among the cultivars which presented better values for acidity (higher or equal to 0.3 g citric acid 100 g-1) were RPT 1095, AG 45, H 9553 and Hypeel 45.
Keywords: Fruit quality; Industry; Lycopersicon esculentum Mill.